Determinants of Audit Quality for Companies Listed on the London Stock Exchange - Zech, Krzysztof (2010)
Policymakers and regulators have been concerned about the role and value of external auditors and their independence. Using a large sample of the UK’s largest companies over the period 2004-2009 this paper investigates determinants of audit quality. For empirical tests, audit quality is measured by abnormal accruals estimated by Ball and Shivakumar (2006) model and Jones (1991) model. Consistent with theoretical predictions auditee risk and auditor tenure are found to have a positive impact on audit quality. The results also show that client-auditor affiliations and client importance issues create opportunities for earnings management and hence decrease the quality of audit services. In conjunction with mixed impacts of audit and non-audit service fees, obtained relations provide further support to the debate surrounding excessive fees paid to auditors. Finally, empirical tests reveal that audit quality is indifferent among industry specialist auditors or Big 4 and non-Big 4 accounting firms.